Enteric parasitosis in northern Thailand dairy heifers and heifer calves - Padungtod P. (2014)
A cross-sectional study was designed to: (1) determine the prevalences of enteric parasitic infections in dairy heifers and heifer calves (Bos taurus) in northern Thailand, and (2) determine the risk factors associated with the observed prevalences of infection. A stratified random sample of 87 farms was selected for study, and fecal and blood samples were collected from 439 out of 450 heifers and heifer calves from these farms. Fecal samples were processed by floatation and modified Benedek sedimentation methods, and then examined microscopically for the presence of enteric parasitic ova. Complete blood counts typically were within the reference range (done using standard methods). The overall prevalence for enteric parasites in heifers and heifer calves was 54%; most were of trematodes (41%) and nematodes (26%). Risk-factors analysis at the farm level yielded no significant results. Increased age significantly increased the odds of enteric parasite infection (OR = 1.02, 95% CI 1.01-1.04). © 2001 Elsevier Science B.V.